Study of physical properties of cobalt substituted Pr0.7Ca0.3MnO3 ceramics. Issue 5 (April 2016) - M'nassri, R.; Khelifi, M.; Rahmouni, H.; Selmi, A.; Khirouni, K.; Chniba-Boudjada, N.; Cheikhrouhou, A.
Abstract: An investigation on single phase semiconducting polycrystalline Pr0.7 Ca0.3 MnO3 and Pr0.7 Ca0.3 MnCo0.1 O3 crystallized in the orthorhombic system with Pnma space group is reported. We found that σ DC increases when introducing Co for T <110 K but for T >110 K, it decreases. Also, the contribution of hopping process in conduction mechanism was in agreement with the Jonscher law and Mott theory. Capacitance was extensively dependent on temperature and frequency. A dielectric transition was observed at T =150 K for the doped compound. The temperature dependence of dielectric permittivity is well described by Curie–Weiss law. The parameter of deviation from Curie–Weiss behavior to modified Curie–Weiss law is found to be Δ T m =30 K. The substitution of Mn by Co was found to destroy the charge order state observed in the parent compound and to induce a ferromagnetic phase at low temperature. The cobalt-substituted sample exhibits a maximum value of magnetic entropy change |∆ S max |=3.2 J kg −1  K −1 and a large relative cooling power with a maximum value of 301 J/kg under an applied field of 5 T. Technically, these large values make the prepared material very promising for magnetic refrigeration.